Performance of mortars based on recycled glass as aggregate by accelerated decay tests (ADT). (20th September 2021) - Alducin-Ochoa, J.M.; Martín-del-Río, J.J.; Torres-González, M.; Flores-Alés, V.; Hernández-Cruz, D.
Graphical abstract: Highlights: Crushed glass aggregates show good performance in accelerated decay tests. Mortars with glass improves significantly against the crystallisation of salts. Glass means a clear improvement in the compression resistance in the decay tests. The ITZs of the glass aggregates develop a lower degree of microcracking. Abstract: The incorporation of crushed glass as a substitute for natural aggregates in mortar and concrete represents a positive impact on the manufacturing processes. The use of glass residues can lead to the improvement of certain properties of sustainable construction products. In these cases, it is important to analyse in detail the behaviour of the material to verify possible applications at an industrial level and contribute to the development of new construction products and solutions. This work studies the behaviour of mortars with recycled glass as a partial replacement of aggregate against common accelerated decay tests, such as salt crystallization, freezing and thermal shock. The influence on the basic physical and mechanical properties has been evaluated by statistical analysis of the results, observing a particularly significant improvement in the resistance of mortars with recycled glass against the expansive action of salt crystallization (>20%). The influence of alteration processes on the internal structure has been analysed by ultrasound transmission tests and its correlation with Young's modulus. The values obtained are in the range of similar materials, having the samples subjected to freezing test a major degree of deterioration. The internal structures have been studied by scanning electron microscopy, observing in samples subjected to salt crystallization tests a greater homogeneity and a lower degree of microcracking in the aggregate/paste interfaces of the glass grains.